2017
DOI: 10.1371/journal.pone.0174907
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of the male reproductive system in a potential bio-indicator species – The marine invertebrate Galeolaria caespitosa (Polychaeta: Serpulidae)

Abstract: For the first time, this study has systemically investigated the male reproductive system in a sessile broadcast-spawning marine invertebrate, Galeolaria caespitosa (Polychaeta: Serpulidae), which has significant potential as a bio-indicator species of coastal marine pollution. The abdomen of G. caespitosa was divided by intersegmental septa into over 80 trunk segments. Each segment served as a germinal chamber with a C-shaped gonadal arrangement consisting of several distinct compartments: a seminiferous epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The results can be applied in ecological risk assessments (ERA), to yield Species Sensitivity Distributions (SSDs), which model species sensitivity to chemicals or other stressors (Posthuma et al, 2002) (Tulloch et al, 2016b) (Liu et al, 2014). At the border between organismal and population levels, alterations on growth and development, reproduction and behavior, are issues of concern: tests on fish, birds, terrestrial and aquatic invertebrates, terrestrial and aquatic macrophytes, and microscopic plants are commonly part of monitoring campaigns (Kapustka, 2003) (Moro et al, 2014) (Gauthier et al, 2016) (Schwindt, 2015) (Lu et al, 2017) (Díaz-Gil et al, 2017 (Gür et al, 2016) (Gopalapillai et al, 2014) (van Wijngaarden and Arts, 2018).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…The results can be applied in ecological risk assessments (ERA), to yield Species Sensitivity Distributions (SSDs), which model species sensitivity to chemicals or other stressors (Posthuma et al, 2002) (Tulloch et al, 2016b) (Liu et al, 2014). At the border between organismal and population levels, alterations on growth and development, reproduction and behavior, are issues of concern: tests on fish, birds, terrestrial and aquatic invertebrates, terrestrial and aquatic macrophytes, and microscopic plants are commonly part of monitoring campaigns (Kapustka, 2003) (Moro et al, 2014) (Gauthier et al, 2016) (Schwindt, 2015) (Lu et al, 2017) (Díaz-Gil et al, 2017 (Gür et al, 2016) (Gopalapillai et al, 2014) (van Wijngaarden and Arts, 2018).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Males' germ cells originate from the seminiferous epithelium and are released into the coelom at an early stage (Dales, 1950). Lu, Aitken, and Lin (2017) found that the spermatids consisted of paired spermatocytes connected by a cytoplasmic bridge. Spermatids in early development were without tails, which developed over time.…”
Section: Gametogenesis Of H Diversicolormentioning
confidence: 99%
“…According to previous studies from our laboratory, the entire process of spermiogenesis in G . gemineoa occurs while the gametes are floating freely in the lumen of the germinal chamber unattached to nurse cells of any kind [ 20 ]. Such independence from supporting cells makes spermiogenesis in G .…”
Section: Introductionmentioning
confidence: 99%